'Global Islamic Marketing Conference (GIMC): challenge, investment' (20-22 March 2011 Dubai, United Arab Emirates) - Kayadibi, Saim (International Institute of Advanced Studies (IAIS) Malaysia and Pluto Press (London), 2012)
The first Global Islamic Marketing Conference (GIMC): Challenge, Investment, held at Park Hyatt Dubai resort hotel from 20-22 March 2011, was a great opportunity the 170 local and international researchers and scholars from around the world to meet each other. The eighty-five presented working papers made this one of the region’s most successful academic and international events. Local and international media outlets and government representatives, as well as H.H. Sheikh Nahayan Al Nahayan (chancellor, United Arab Emirates University [UAEU]) and H.E. Fatima Alshamsi (secretary general, UAEU) also attended.